PENGARUH STRES KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN (STUDI KASUS PADA KARYAWAN PT. NUSANTARA SURYA SAKTI (NSS) KOTA BENGKULU) - Safutra, Effan; Herfianti, Meiffa (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
Turnover intention is the intention or desire of employees to leave the company where they currently work voluntarily and consciously. Some of the factors that influence turnover intention are job stress and job satisfaction. This study aims to determine the effect of job stress and job satisfaction on turnover intention. This type of research is quantitative research with a descriptive approach. The population of this research is all employees of PT Nusantara Surya Sakti (NSS) Bengkulu City. The number of research samples was 63 people. Data collection was done using a questionnaire. Data analysis techniques using multiple linear regression analysis techniques. The results of data analysis obtained multiple linear regression equations as follows: Y = 23.125 + 0.298 X1 - 0.336 X2. The results of the analysis show that partially job stress has a positive and significant effect on turnover intention (tcount = 5.619 and Sig = 0.000) and job satisfaction has a negative and significant effect on turnover intention (tcount = -6.407 and Sig = 0.000). Simultaneously, there is an effect of job stress and job satisfaction on turnover intention.nIt is recommended to the management of PT. NSS Bengkulu City to be able to reduce the level of turnover intention in employees by reducing the level of job stress and increasing employee job satisfaction. Keywords: Turnover Intention, job stress, job satisfaction